Factors Associated with a Return Visit among Patients with Infection after Discharged from an Emergency Department: An Integrative Literature Review - Dumthong, Jirarat; Damkliang, Jintana (Journal of Research in Nursing-Midwifery and Health Sciences, 2024)
Introduction: A return visit to the emergency department (ED) is an indicator for quality and patient safety, especially among patients with infection. A patient who return visit to the ED indicates an increase in the severity of infection and may be a cause of death. The objective of this study was to analyze factors associated with a return visit among patients with infection after discharged from the ED. Methods: An integrative literature review was conducted by studying research articles published in Thai and international journals on the database, including PubMed, Academic Search Ultimate, EMBASE on Ovid, Scopus, ProQuest, Cochrane, Web of Science, WILEY Online Library and Science Direct between 2013 and 2023. A total of 10 articles with full-text met the inclusion criteria. The quality of research articles was evaluated using critical appraisal tools developed by Joanna Briggs Institute. An interrater reliability was conducted by 2 evaluators and yield 100%. Data were analyzed using descriptive statistics. Results: Factors associated with a return visit among patients with infection after discharged from the ED, including age, signs and symptoms, level of severity, abnormal of vital signs, abnormal of laboratory results, sites of infection, misdiagnosis, and not receiving advice and following up on symptoms. Conclusion: The results of this study can be used as information to develop a discharge planning model for patients with sepsis or suspected sepsis admitted to the ED. The model can be used as a guideline for giving advice and continuously monitoring patients’ symptoms, and to prevent the severity of the infection, and reduce the rate of a return visit to the ED.